Pendampingan Pembelajaran Kaidah Nahwu dengan Kitab Al-Ajurumiyyah di Pondok Pesantren Darus Sibyan Jombang Jember - Mannan, Ahmad Mizan Rosyadi Abdul Jalil; Hidayah, Muhammad Shokhibul (INAIFAS Press, 2023)
Learning Nahwu rules is very urgent in islamic boarding schools whose notabe only focuses on Tahfidzul Qur'an because without understanding Nahwu rules students will not understand the Quran and Arabic texts, Mapping material in Nahwu science is one alternative to make it easier to master it in beginner-level students. The purpose of this community service activity is assistance to the students of the Darus Sibyan Islamic Boarding School in learning Nahwu knowledge which is focused on Nahwu rules. Guidance assistance to students uses the community development method by prioritizing observation and documentation. The implementation strategy, namely (1) preparation; (2) implementation of activities and (3) evaluation of activities. As a result of the changes, assisted subjects can understand the description of Nahwu science, be awake from errors in speech and writing, strengthen the potential for memory and easily memorize Nahwu rules.